The Influence of Compensation and Employee Engagement on Employee Performance: A Study at Bogor Hospital - Aza El Munadiyan; Ikmal (YCMM, 2026)
Human resource management literature indicates that compensation and employee engagement are two important factors influencing employee performance. However, empirical findings in the healthcare sector, particularly in developing countries, remain inconsistent. This study aims to analyze the influence of compensation and employee engagement on employee performance at Bogor Hospital in Bogor. This study used a quantitative approach with an associative design. Data were collected through a Likert-scale questionnaire from 55 permanent employees and analyzed using validity and reliability tests, simple and multiple linear regression, t-tests, F-tests, Pearson correlation, and the coefficient of determination. The results showed that compensation had a positive and significant effect on employee performance, while employee engagement had a positive but insignificant effect in the multiple regression model. Simultaneously, both variables significantly influenced employee performance, contributing 46.0%. The novelty of this study lies in the finding that, in the context of private hospitals in Indonesia, compensation plays a more dominant role than employee engagement, contrasting with the dominant findings in Western literature that position engagement as the primary predictor of performance. This research contributes to the literature on contextual human resource management and provides strategic implications for HR management in the healthcare sector.